Neonatal Pneumothorax in Late Preterm and Full-Term Newborns with respiratory Distress: A Single-Center Experience - Eun-Ah Kim; Jae-Hun Jung; Sang-Yoon Lee; Sook-Hyun Park; Ji Sook Kim (Korean Society of Neonatology, 2022)
Purpose To evaluate the incidence rate, clinical characteristics, and perinatal outcomes of pneumothorax in late preterm and full-term newborns with respiratory distress and analyze the risk factors associated with pneumothorax. Methods Infants born at ≥34 weeks' gestation with respiratory distress and pneumothorax admitted between February 2014 and December 2020 were enrolled in this study. The pneumothorax group (n=36) was matched to the control group (n=144) in a 1:4 ratio, based on gestational age and birth weight. Risk factors were identified using logistic regression analysis with backward stepwise selection. Results The incidence of pneumothorax during the study period was 1.36% (38/2,788). All patients were diagnosed with pneumothorax within 48 hours after birth, and increased oxygen demand was the most common symptom. The proportion of mortality and perinatal morbidity, such as intraventricular hemorrhage ≥grade 3, was significantly higher in the pneumothorax group than in the control group. The risk factors associated with pneumothorax were the need for positive pressure ventilation in the delivery room (odds ratio [OR], 3.40; 95% confidence interval [CI], 1.26 to 9.12; P=0.015) and a higher fraction of inspired oxygen to achieve an oxygen saturation of ≥90% on admission (OR, 1.06; 95% CI, 1.03 to 1.09; P<0.001). Conclusion Pneumothorax should be suspected in late preterm and full-term newborns with respiratory distress within the first 3 days of life. Based on these risk factors, early diagnosis can reduce perinatal mortality and morbidity.